MicroRNA‐379 couples glucocorticoid hormones to dysfunctional lipid homeostasis - Guia, Roldan M. de; Rose, Adam J.; Seibert, Oksana; Strzoda, Daniela; Zota, Annika; Feuchter, Yvonne; Krones-Herzig, Anja; Kirilov, Milen; Sticht, Carsten; Gretz, Norbert; Diederichs, Sven; Berriel Diaz, Mauricio; et al. (The EMBO journal, 2015)
In mammals, glucocorticoids (GCs) and their intracellular receptor, the glucocorticoid receptor (GR), represent critical checkpoints in the endocrine control of energy homeostasis. Indeed, aberrant GC action is linked to severe metabolic stress conditions as seen in Cushing's syndrome, GC therapy and certain components of the Metabolic Syndrome, including obesity and insulin resistance. Here, we identify the hepatic induction of the mammalian conserved microRNA (miR)‐379/410 genomic cluster as a key component of GC/GR‐driven metabolic dysfunction. Particularly, miR‐379 was up‐regulated in mouse models of hyperglucocorticoidemia and obesity as well as human liver in a GC/GR‐dependent manner. Hepatocyte‐specific silencing of miR‐379 substantially reduced circulating very‐low‐density lipoprotein (VLDL)‐associated triglyceride (TG) levels in healthy mice and normalized aberrant lipid profiles in metabolically challenged animals, mediated through miR‐379 effects on key receptors in hepatic TG re‐uptake. As hepatic miR‐379 levels were also correlated with GC and TG levels in human obese patients, the identification of a GC/GR‐controlled miRNA cluster not only defines a novel layer of hormone‐dependent metabolic control but also paves the way to alternative miRNA‐based therapeutic approaches in metabolic dysfunction.